The influence of social media marketing, product quality, and price on purchase decisions in mid covid-19 on Ilsproject - Ni Made Pertiwi Winasari (Review of Management, Accounting, and Business Studies, 2021)
The COVID-19 pandemic that has occurred in Indonesia has changed all the orders of people's lives, one of which is the change from offline to online. Various industries have adopted online marketing in the midst of uncertainty due to the pandemic and intense competition, one of which is Ilsproject. This study aims to analyze and determine the effect of social media marketing, product quality, and price on consumer purchasing decisions in the midst of a pandemic. This research is quantitative, so the data collection method is done by questionnaire and analyzed using a multiple linear regression analysis approach. The findings in this study reveal that the variables of social media marketing, product quality, and price have a positive and significant effect on purchasing decisions, either partially or simultaneously. Thus, this research is able to contribute theoretically to the marketing literature and practically to Ilsproject as input for decision-making related to strategic planning in the future.